Novel achiral four-ring bent-shaped nematic liquid crystals with trifluoromethyl and methyl substituents in the central molecular core: an unusually large Kerr constant in blue phase III of nematic-chiral dopant mixture. Issue 27 (26th June 2017) - Khan, R. K.; Turlapati, S.; Rao, N. V. S.; Pratibha, R.; Drzewinski, W.; Dabrowski, R.; Ghosh, S.
Abstract : Stable BPIII with unusually large Kerr constant is derived from four-ring bent-core nematic liquid crystals comprising a trifluoromethyl phenyl core. Abstract : Here, we report the first example of achiral bent-shaped liquid crystals comprising trifluoromethyl and methyl moieties on adjacent phenyl rings in the core, exhibiting nematic mesomorphism close to room temperature on cooling. The XRD confirms the existence of cybotactic clusters in the nematic phase. Strong hydrodynamic instabilities at relatively low voltage in the parent compound suggest a low threshold voltage for electro-optic (E-O) performance. Furthermore, a wide-temperature blue phase III with a stable electro-optic Kerr response has been developed by these novel bent-core molecules. The E-O study reveals the highest Kerr constant value along with a low voltage for obtaining maximum transmission, among the BPIII systems reported so far.